Ảnh hưởng của thông tin miễn nhiệm nhân sự cấp cao đến giá cổ phiếu - Võ Xuân Vinh; Đặng Bửu Kiếm (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This paper investigates the impact of the dismissal announcements of top managers, including the board of directors (BoD) and the board of management (BoM), on stock prices. Our sample includes the dismissal announcements of BoD and BoM of listed companies on the Ho Chi Minh City Stock Exchange during the period from January 2008 to March 2016. By employing event study method, our results show that the stock prices fall before the BoD dismissal announcement date. There is no excess change in stock prices on the event date; however, they have recovered technically after the event date. Furthermore, the study finds no evidence of excess change in stock prices during the event date of BoM dismissals. Leaked news before the announcement date and the change in stock prices in short term are also important findings in this paper.
Keywords: Dismissal announce-ments; Board of director (BoD); Board of man-agement (BoM); Event study; Abnormal returns